A sex-specific pathway linking early life maltreatment, vagal activity, and depressive symptoms - Sigrist, Christine; Ottaviani, Cristina; Baumeister-Lingens, Luise; Bussone, Silvia; Pesca, Chiara; Kaess, Michael; Carola, Valeria; Koenig, Julian (European journal of psychotraumatology, 2024)
Background: Experiences of early life maltreatment (ELM) are alarmingly common and represent a risk factor for the development of psychopathology, particularly depression. Research has focused on alterations in autonomic nervous system (ANS) functioning as a mediator of negative mental health outcomes associated with ELM. Early alterations in autonomic vagal activity (vmHRV) may moderate the relationship between ELM and depression, particularly when considering forms of emotional maltreatment. Recent evidence suggests that the relationships of both ELM and vmHRV with depression may be non-linear, particularly considering females. Objective: Building on and extending theoretical considerations and previous work, the present work aims to further the current understanding of the complex relationships between ELM exposure, vmHRV, and depression. Methods: This study uses an adaptive modelling approach, combining exploratory network-based analyses with linear and quadratic moderation analyses, drawing on a large sample of males and females across adolescence (total N = 213; outpatient at-risk sample and healthy controls) and adulthood (total N = 85; community-based convenience sample). Results: Exploratory network-based analyses reveal that exposure to emotional abuse is particularly central within a network of ELM subtypes, depressive symptoms, and concurrent vmHRV in both adolescents and adults. In adults, emotional neglect shows strong associations with both emotional abuse and vmHRV and is highly central as a network node, which is not observed in adolescents. Moderator analyses reveal significant interactions between emotional maltreatment and vmHRV predicting depressive symptoms in adult females. Significant quadratic relationships of emotional maltreatment and vmHRV with depression are observed in both adolescent and adult females. Conclusions: The present findings contribute to the understanding of the psychological and physiological mechanisms by which ELM acts as a risk factor for the development of depression. Ultimately, this will contribute to the development of targeted and effective intervention strategies to mitigate the detrimental effects of early adversity. Early exposure to chronic and severe adversity, which includes experiences of maltreatment, defined by the World Health Organization as physical, sexual, emotional abuse and/or neglect of children under the age of 18, is highly prevalent in the general population (estimated at 40-50 percent), and is a well-documented risk factor for depression.The present work combines network-based analyses with tests of different functions (i.e. linear, nonlinear quadratic) in moderator analyses to further explore the complex relationships among ELM exposure, vmHRV, and depression.The present findings contribute to the understanding of the psychological and physiological mechanisms by which early exposure to chronic and severe maltreatment acts as a risk factor for the development of depression.Ultimately, this will contribute to the development of targeted and effective intervention strategies to mitigate the detrimental effects of early adversity. Early exposure to chronic and severe adversity, which includes experiences of maltreatment, defined by the World Health Organization as physical, sexual, emotional abuse and/or neglect of children under the age of 18, is highly prevalent in the general population (estimated at 40-50 percent), and is a well-documented risk factor for depression. The present work combines network-based analyses with tests of different functions (i.e. linear, nonlinear quadratic) in moderator analyses to further explore the complex relationships among ELM exposure, vmHRV, and depression. The present findings contribute to the understanding of the psychological and physiological mechanisms by which early exposure to chronic and severe maltreatment acts as a risk factor for the development of depression. Ultimately, this will contribute to the development of targeted and effective intervention strategies to mitigate the detrimental effects of early adversity.